Genomic diversity of group A rotaviruses from wild boars and domestic pigs in Japan: wide prevalence of NSP5 carrying the H2 genotype - Shizawa, Shigeki; Fukuda, Fujiko; Kikkawa, Yasuhiro; Oi, Toru; Takemae, Hitoshi; Masuda, Tsuneyuki; Ishida, Hiroho; Murakami, Hironobu; Sakaguchi, Shoichi; Mizutani, Tetsuya; Nagai, Makoto; Oba, Mami (Archives of virology, 2024)
Group A rotavirus (RVA) sequences were detected in 10.8% (23/212) and 20.7% (87/421) of fecal samples collected in 2017-2022 from wild boars and domestic pigs, using next-generation sequencing. Complete genome sequence analysis of one wild boar and 13 domestic pig RVAs revealed that six of them carried the rare H2 NSP5 genotype. Out of the 39 samples for which the NSP5 genotype could be determined, 23 (59.0%) were of genotype H2. H2 porcine RVAs consist exclusively of Japanese porcine RVAs and exhibit sequence diversity in each segment, suggesting that H2 porcine RVAs may have evolved through reassortment within the Japanese pig population.